2010
DOI: 10.4314/bajopas.v1i1.57503
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of Pulmonary Tuberculosis (PTB) prevalence amongst patients attending infrectious diseases hospital, in Kano, Nigeria

Abstract: A retrospective study aimed at ascertaining the prevalence of Pulmonary TB amongst patients attending Infectious Diseases Hospital, Kano was conducted between January, 2006 and July, 2008. Sputum samples were obtained from three thousand six hundred and seventy nine (3679) patients. Samples were smeared on glass slides, stained using Ziehl Neelsen Stain and later observed under light (oil immersion) microscopy. The results showed that were positive for tuberculosis had prevalence of 541 (14.7%) out of 3679 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
8
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 1 publication
5
8
1
Order By: Relevance
“…Age groups of 15-44 years were affected more than the other age groups, which is consistent with WHO (2012) report. This is also is in agreement with the reports of other previous studies (Shargie and Lindtjorn, 2005;Imam and Oyeyi, 2008;Datiko and Lindtjørn, 2009;Tessema et al, 2009;Jetan et al, 2010;Ejeta et al, 2012;Prakasha et al, 2012;Biadglegne et al, 2013).This may be due to the fact that this age group is sexually active and hence infected with HIV, which predispose this group to TB. The proportions of the different types of TB recorded in were similar with those reported (Kassu et al, 2007;Tessema et al, 2009;Biadglegne et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Age groups of 15-44 years were affected more than the other age groups, which is consistent with WHO (2012) report. This is also is in agreement with the reports of other previous studies (Shargie and Lindtjorn, 2005;Imam and Oyeyi, 2008;Datiko and Lindtjørn, 2009;Tessema et al, 2009;Jetan et al, 2010;Ejeta et al, 2012;Prakasha et al, 2012;Biadglegne et al, 2013).This may be due to the fact that this age group is sexually active and hence infected with HIV, which predispose this group to TB. The proportions of the different types of TB recorded in were similar with those reported (Kassu et al, 2007;Tessema et al, 2009;Biadglegne et al, 2013).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, it was observed that males comprise the higher proportion of TB compared to females. (Shargie and Lindtjorn, 2005;Imam and Oyeyi, 2008;Datiko and Lindtjørn, 2009;Jetan et al, 2010;Berhe et al, 2012;Ejeta et al, 2012;Biadglegne et al, 2013). Age groups of 15-44 years were affected more than the other age groups, which is consistent with WHO (2012) report.…”
Section: Discussionmentioning
confidence: 99%
“…born means such as coughing, sneezing, spitting and even speaking [2]. The comprehensive investigations on hematological changes and abnormalities associated to tuberculosis is still lacking.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusive Criteria for the study is that Pulmonary tuberculosis patients, diagnosed of pulmonary tuberculosis based on clinical and biological evidence of smear positive for acid fast bacilli by Ziehl -Neelsen Staining [2]. Freshly diagnosed and treated patients, Including the smokers, alcoholics & diabetic patients.…”
Section: Methodsmentioning
confidence: 99%
“…WHO [2] reported that 98% of tuberculosis deaths occurred in the developing world, affecting mostly young adults in their productive ages. Despite efforts made, globally or nationally to curb the effects of TB, different studies have shown that the trend of pulmonary TB remained as a health problem in the world [3][4][5][6][7]. In 2013, WHO [8] reported a decline in the impact of tuberculosis by the year 2012.…”
Section: Introductionmentioning
confidence: 99%